Factors influencing participation in health behaviors in endometrial cancer survivors. Issue 8 (10th October 2016) - Hardcastle, Sarah J.; Glassey, Rachael; Salfinger, Stuart; Tan, Jason; Cohen, Paul
Abstract: Background: The study purpose was to investigate endometrial cancer survivors' health perceptions following cessation of active cancer treatment and to explore factors influencing participation in health‐promoting behaviors. Methods: Face‐to‐face interviews were conducted with participants who had completed active treatment of cancer within the previous 3 years. Participants were 22 endometrial cancer survivors (mean age = 62.55 years, SD = 7.08) at risk of cardiovascular disease who were recruited from 2 oncologists in Perth, Western Australia. Interview transcripts were analyzed using thematic analysis. Results: Five main themes emerged: physical activity knowledge and advice; authority of oncologists; accountability and external motivation; monitoring and barriers to healthy eating; and physical activity. Participants recalled that specific recommendations for physical activity or body weight were rarely made by the oncologists, but felt they would have followed such lifestyle advice if it had been given. The overarching theme was the need for accountability and monitoring to successfully change health behaviors. Conclusions: Interventions aimed at promoting health behaviors in endometrial cancer survivors should include referral and advice from oncologists, provision of monitoring, and promotion of planning and self‐control. Implications for endometrial cancer survivors at risk of cardiovascular disease: these women are likely to benefit most from interventions aimed at promoting planning, self‐regulation and problem solving and regular follow‐up.